Effect of rotary or manual instrumentation, with or without a calcium hydroxide/1% chlorhexidine intracanal dressing, on the healing of experimentally induced chronic periapical lesions - De Rossi, A.; Silva, LAB; Leonardo, M. R.; Rocha, L. B.; Rossi, M. A. (Mosby, Inc, 2005)
Objective. To evaluate the healing of experimentally induced chronic periapical lesions in dogs at 30, 75, and 120 days after root canal instrumentation with rotary NiTi files or manual K-files, with or without a calcium hydroxide/1% chlorhexidine paste intracanal dressing.Study design. The second, third, and fourth mandibular premolars and the second and third maxillary premolars of 5 dogs (12 to 18 months of age, weighing 8 to 15 kg) were selected for treatment (a total of 82 root canals). After pulp removal, the root canals were left exposed to the oral cavity for 7 days to allow microbial contamination, after which the root canals were sealed with ZOE cement until periapical lesions were confirmed with radiography. Group I and II teeth were instrumented with manual K-files using the crown-down technique. In group III and IV teeth, NiTi rotary files were used. The apical delta was perforated by using #20 to #30 K-files at the length of the tooth, thus creating a standardized apical opening. The apical stop was enlarged to size 70, with 2.5% sodium hypochlorite irrigation at each file change. Teeth in groups II and IV were dressed with calcium hydroxide (Ca(OH)(2))/1% chlorhexidine (CHX) paste for 15 days before root filling. Group I and III teeth did not receive an intracanal dressing. The access openings of the teeth were permanently restored with silver amalgam condensed on a glass ionomer cement base. Pairs of standardized periapical radiographs were taken at the beginning of the treatment (0 days) and at 30, 75, and 120 days after filling.Results. There was no significant difference in the rate of radiographic healing of the periapical lesions between manual and rotary instrumentation. Radiographs taken at 120 days showed that the treatment with Ca(OH)(2)/1% CHX paste resulted in a significant reduction in mean size of the periapical lesions in comparison to single-session treatment. These findings were also true for histologic observations.Conclusion. The findings support the hypothesis that, regardless of the instrumentation technique (manual or rotary), the use of an intracanal dressing is important in the endodontic treatment of dog's teeth with experimentally induced chronic periapical lesions.